A PLA and PPC composite material with isolation structure and preparation method thereof
By adding flexible biodegradable polyester PPC to the polylactic acid material and using a two-step melt blending method to prepare PLA and PPC composite materials with isolation structures, the problems of insufficient brittleness and barrier properties of polylactic acid materials are solved, and composite materials with high toughness and high barrier properties are achieved, which are suitable for industrial applications.
Patent Information
- Application Number
- CN202310488549.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-05-04
AI Technical Summary
The brittleness and poor barrier properties of existing polylactic acid materials limit their application range, and there are technical difficulties in industrial applications of multi-layer composite and nanocomposite methods.
By adding flexible biodegradable polyester PPC with better compatibility to the PLA, and using a two-step melt blending method to prepare PLA and PPC composite material with an isolation structure, the OMMT is mainly dispersed at the interface between PLA and PPC to exert its barrier properties.
It realizes the high toughness and high barrier properties of PLA composite materials, has low cost, simple preparation process, is suitable for industrial applications, and maintains good biodegradability.
Smart Images

Figure CN116444967B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a PLA and PPC composite material with an isolation structure and a preparation method thereof. Background Art
[0002] Polylactic acid (PLA) is an environmentally friendly material derived from biomass. Its monomers come from lactic acid obtained from plant starch fermentation. It can be completely converted into carbon dioxide and water by microbial decomposition in the environment. It has good biocompatibility and biodegradability and is widely used in agricultural films, food packaging and medical materials. PLA has good mechanical strength and transparency, but its inherent brittleness and poor barrier properties severely limit its application range.
[0003] In the existing technology, multi-layer composite and nano-composite methods are often used to improve the barrier performance of polylactic acid. Invention patent CN 115433383 discloses a multi-layer polylactic acid barrier film and its preparation method. The patent uses D-lactide and diacetyl cellulose to graft to obtain CDA-g-PDLA graft copolymer, and then uses polylactic acid and CDA-g-PDLA as raw materials to prepare a multi-layer barrier film. Invention patent CN105729967 discloses a multi-layer polylactic acid composite barrier high-strength film, whose structure consists of an outer layer of polylactic acid hydrophobic strength film, an intermediate layer of polylactic acid barrier film layer and a bottom layer of polylactic acid elastic film, and a hot melt adhesive film layer is provided between each layer of the film. Invention patent CN 113354853 discloses a biodegradable high-barrier antibacterial composite film. The patent uses nanocellulose, barrier agent and antibacterial agent to blend with polylactic acid to prepare a biodegradable high-barrier antibacterial composite film.
[0004] The above patents have made some progress in improving the barrier properties of polylactic acid, but there are still many technical difficulties for industrial application. For example, multi-layer co-extruded polylactic acid film has high requirements for industrial equipment; nanofillers are difficult to disperse in the matrix, and the solution must be pre-prepared for high-speed stirring and centrifugal freeze-drying, which is difficult to mass produce. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the present invention provides a PLA and polypropylene carbonate (PPC) composite material with an isolation structure and a preparation method thereof. The polylactic acid barrier film prepared by the method has high toughness and high barrier performance, low cost, simple preparation process, and is conducive to industrialization.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A PLA and PPC composite material with an isolation structure comprises raw materials in parts by weight: 30-70 parts of PLA, 30-70 parts of PPC and 0.5-5 parts of organic modified montmorillonite (OMMT), and the total weight of the PLA and PPC is 100 parts.
[0008] Furthermore, the raw materials include, by weight: 50 parts of PLA, 50 parts of PPC and 1.5 parts of OMMT.
[0009] The preparation method of the PLA and PPC composite material with an isolation structure comprises the following steps: pre-melting PPC and OMMT, extruding and granulating to obtain modified PPC; and then mixing PLA and modified PPC, extruding and granulating to obtain the PLA and PPC composite material with an isolation structure.
[0010] Furthermore, PPC and OMMT are pre-melted and extruded into granules, wherein the extruder adopts a staged heating method from the feeding zone to the head zone, which is divided into seven sections, the temperature of zone one is 70-100°C, the temperature of zone two is 90-120°C, the temperature of zone three is 110-140°C, the temperature of zone four is 130-145°C, the temperature of zone five is 135-150°C, the temperature of zone six is 130-145°C, the temperature of zone seven is 125-145°C, and the screw speed is 350-500r / min.
[0011] Furthermore, PLA and modified PPC are mixed and extruded into granules, wherein the extruder adopts a staged heating method from the feeding zone to the head zone, which is divided into seven sections, the temperature of zone one is 130-150°C, the temperature of zone two is 150-165°C, the temperature of zone three is 160-180°C, the temperature of zone four is 160-185°C, the temperature of zone five is 165-200°C, the temperature of zone six is 160-190°C, the temperature of zone seven is 160-185°C, and the screw speed is 200-500r / min.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] 1) The present invention adds a flexible biodegradable polyester PPC with good compatibility with PLA to solve the problems of poor toughness and low barrier properties of PLA; and the present invention prepares a PLA and PPC composite material with an isolation structure by a two-step melt blending method, so that OMMT is mainly dispersed at the interface between PLA and PPC, which can better exert the barrier properties of OMMT.
[0014] 2) The polylactic acid composite of the present invention maintains good biodegradability and is environmentally friendly.
[0015] 3) The manufacturing process is simple and the manufacturing cost is low. It can be well applied in the field of environmentally friendly composite membranes and meet the production needs of the polymer materials industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD spectra of the blends prepared in Example 3, Comparative Example 3 and Comparative Example 4 are shown.
[0017] Figure 2 These are cross-sectional SEM images of the blends prepared in Example 3, Comparative Example 3, and Comparative Example 4, wherein a is a cross-sectional SEM image of Example 3, b is a cross-sectional SEM image of Comparative Example 3, and c is a cross-sectional SEM image of Comparative Example 4. DETAILED DESCRIPTION
[0018] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0019] The present invention provides a PLA and PPC composite material with an isolation structure, wherein the raw materials include, by weight, 30-70 parts of PLA, 30-70 parts of PPC and 0.5-5 parts of OMMT, and the total weight of the PLA and PPC is 100 parts. The PLA and PPC composite material with an isolation structure prepared in the present application has high toughness and oxygen barrier performance, can be degraded, and the obtained composite material can meet the needs of high-toughness food, medicine and other fields.
[0020] The preparation method of the PLA and PPC composite material with an isolation structure of the present invention comprises the following steps: pre-melting and extruding PPC and OMMT into granules, and the extruder adopts a segmented heating method from a feeding zone to a head zone, which is divided into 7 sections, the temperature of the first zone is 70-100°C, the temperature of the second zone is 90-120°C, the temperature of the third zone is 110-140°C, the temperature of the fourth zone is 130-145°C, the temperature of the fifth zone is 135-150°C, the temperature of the sixth zone is 130-145°C, the temperature of the seventh zone is 125-145°C, and the screw speed is 350-500r / min , to obtain modified PPC; then PLA and modified PPC are mixed and extruded into granules, the extruder adopts a staged heating method from the feeding zone to the head zone, which is divided into 7 sections, the temperature of zone one is 130-150°C, the temperature of zone two is 150-165°C, the temperature of zone three is 160-180°C, the temperature of zone four is 160-185°C, the temperature of zone five is 165-200°C, the temperature of zone six is 160-190°C, the temperature of zone seven is 160-185°C, the screw speed is 200-500r / min, and a PLA and PPC composite material with an isolation structure is obtained.
[0021] In the following examples, the twin-screw extruder is used for melt extrusion granulation, and a single-screw extruder or a kneader can be selected according to actual needs.
[0022] The composite material extruded from the twin-screw extruder is cooled and then granulated to obtain composite material particles. The cooling method is preferably air cooling; and the granulation method is preferably pelletizing.
[0023] In the following examples, PLA was purchased from NatureWorks, PPC was purchased from Jiangsu Zhongke Jinlong Chemical Co., Ltd., and OMMT (Cloisite 30B) was purchased from Southern Clay Products.
[0024] For the sake of clarity, the present invention is described in detail through the following examples and comparative examples.
[0025] In the following embodiments and comparative examples provided by the present invention, in order to evaluate the performance of the prepared composite material, the prepared composite material was hot-pressed on a flat vulcanizer at 180° C. and a pressure of 10 MPa, and then quickly cooled to room temperature by a cold press to obtain sheets of different thicknesses for different performance tests, as follows:
[0026] Unless otherwise specified, the raw materials used in the present invention are all from common commercially available medicines in this field. The instruments and devices used in the present invention are also conventional instruments and equipment in this field. The mechanical property test method involved in the present invention is: in accordance with the GB / T1040-2018 standard, the tensile strength, modulus and elongation at break of the composite are measured using the Instron-1121 tester, the tensile rate is 10mm / min, and the average value of 5 groups of valid data is taken for each group of sample tests. The index oxygen permeability coefficient test method involved in the present invention is: in accordance with the ASTM D3985 standard, the oxygen permeability of the composite is measured using a VAC-V2 oxygen permeation tester, the test temperature is 23°C, the humidity is 0RH%, and 3 parallel samples are tested for each group of samples.
[0027] Example 1
[0028] Preparation of 50PLA-0.5T degradable high barrier composite
[0029] 10kgPPC and 0.1kgOMMT were mixed, and the modified PPC masterbatch was obtained by melt extrusion granulation with a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 70℃, 90℃, 110℃, 130℃, 135℃, 130℃, 125℃, and the speed was 350r / min. The materials were mixed and granulated, air-cooled, and pelletized. 5.05kg of the dried modified PPC masterbatch and 5kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 140℃, 155℃, 170℃, 178℃, 182℃, 182℃, 180℃, and the speed was 260r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 50 / 50.5.
[0030] Example 2
[0031] Preparation of 50PLA-1T degradable high barrier composite
[0032] 10kgPPC and 0.2kgOMMT were mixed, and the modified PPC masterbatch was obtained by melt extrusion granulation with a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 80℃, 100℃, 120℃, 135℃, 140℃, 135℃, 130℃, and the speed was 400r / min. The materials were mixed and granulated, air-cooled, and pelletized. 5.1kg of the dried modified PPC masterbatch and 5kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 150℃, 165℃, 175℃, 185℃, 190℃, 185℃, 180℃, and the speed was 380r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 50 / 51.
[0033] Example 3
[0034] Preparation of 50PLA-1.5T degradable high barrier composite
[0035] 10kgPPC and 0.3kgOMMT were mixed and melt extruded and granulated by a twin-screw extruder to obtain modified PPC masterbatch. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 90℃, 110℃, 130℃, 140℃, 150℃, 145℃, and 140℃, respectively, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 5.15kg of the dried modified PPC masterbatch and 5kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 150℃, 165℃, 175℃, 185℃, 190℃, 185℃, and 180℃, respectively, and the speed was 320r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 50 / 51.5.
[0036] Example 4
[0037] Preparation of 50PLA-3T degradable high barrier composite
[0038] 10kgPPC and 0.6kgOMMT were mixed and melt extruded and granulated by a twin-screw extruder to obtain modified PPC masterbatch. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 100℃, 120℃, 140℃, 145℃, 150℃, 145℃, 140℃, and the speed was 500r / min. The materials were mixed and granulated, air-cooled, and pelletized. 5.3kg of the dried modified PPC masterbatch and 5kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 140℃, 155℃, 170℃, 178℃, 182℃, 182℃, 180℃, and the speed was 260r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 50 / 53.
[0039] Example 5
[0040] Preparation of 30PLA-5T degradable high barrier composite
[0041] 14kg PPC and 1kg OMMT were mixed, and the modified PPC masterbatch was obtained by melt extrusion granulation with a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 90℃, 110℃, 130℃, 140℃, 150℃, 145℃, and 140℃, respectively, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 7.5kg of the dried modified PPC masterbatch and 3kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 150℃, 165℃, 175℃, 185℃, 190℃, 185℃, and 180℃, respectively, and the speed was 260r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 30 / 75.
[0042] Example 6
[0043] Preparation of 40PLA-1.5T biodegradable high barrier composite
[0044] 12kgPPC and 0.3kgOMMT were mixed and melt extruded and granulated by a twin-screw extruder to obtain modified PPC masterbatch. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 90℃, 110℃, 130℃, 140℃, 150℃, 145℃, and 140℃, respectively, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 6.15kg of the dried modified PPC masterbatch and 6kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 140℃, 155℃, 170℃, 178℃, 182℃, 182℃, and 180℃, respectively, and the speed was 320r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 40 / 61.5.
[0045] Example 7
[0046] Preparation of 60PLA-2T degradable high barrier composite
[0047] 8kg PPC and 0.4kg OMMT were mixed, and the modified PPC masterbatch was obtained by melt extrusion granulation with a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 90℃, 110℃, 130℃, 140℃, 150℃, 145℃, and 140℃, respectively, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 4.2kg of the dried modified PPC masterbatch and 6kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 140℃, 155℃, 170℃, 178℃, 182℃, 182℃, and 180℃, respectively, and the speed was 380r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 60 / 42.
[0048] Example 8
[0049] Preparation of 70PLA-3T degradable high barrier composite
[0050] 6kgPPC and 0.6kgOMMT were mixed and melt extruded and granulated by a twin-screw extruder to obtain modified PPC masterbatch. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 90℃, 110℃, 130℃, 140℃, 150℃, 145℃, and 140℃, respectively, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 3.3kg of the dried modified PPC masterbatch and 7kg of polylactic acid material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 140℃, 155℃, 170℃, 178℃, 182℃, 182℃, and 180℃, respectively, and the speed was 320r / min. The weight ratio of polylactic acid and modified PPC masterbatch was 70 / 33.
[0051] Comparative Example 1
[0052] Preparation of P-50PLA degradable blends
[0053] 5kgPLA and 5kgPPC were mixed, melt-kneaded, granulated, air-cooled and pelletized using a twin-screw extruder. The temperatures of the seven sections of the extruder from the feeding zone to the head zone were 140°C, 155°C, 170°C, 178°C, 182°C, 182°C and 180°C, respectively, and the rotation speed was 450r / min.
[0054] Comparative Example 2
[0055] Preparation of P-PLA-1.5T degradable composite
[0056] 10kgPLA and 0.15kgOMMT were directly mixed, melt-kneaded, granulated, air-cooled and pelletized using a twin-screw extruder. The temperatures of the seven sections of the extruder from the feeding zone to the head zone were 140°C, 155°C, 170°C, 178°C, 182°C, 182°C and 180°C, respectively, and the rotation speed was 320r / min.
[0057] Comparative Example 3
[0058] Preparation of P-50PPC-1.5T degradable high barrier composite
[0059] 10kgPLA and 0.3kgOMMT were mixed and melt extruded and granulated by a twin-screw extruder to obtain modified PLA masterbatch. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 150℃, 165℃, 175℃, 185℃, 190℃, 185℃, 180℃, and the speed was 450r / min. The materials were mixed and granulated, air-cooled, and pelletized. 5.15kg of the dried modified PLA masterbatch and 5kg of PPC material were mixed evenly, mixed and granulated, air-cooled, and pelletized by a twin-screw extruder. The temperature of the seven sections from the feeding zone to the head zone of the extruder was 150℃, 165℃, 175℃, 185℃, 190℃, 185℃, 180℃, and the speed was 320r / min. The weight ratio of PPC and modified polylactic acid masterbatch was 50 / 51.5.
[0060] Comparative Example 4
[0061] Preparation of P-50PLA-1.5T degradable composite
[0062] 5kgPLA, 5kgPPC and 0.15kgOMMT were directly mixed, melt-kneaded, granulated, air-cooled and pelletized using a twin-screw extruder. The temperatures of the seven sections from the feeding zone to the head zone of the extruder were 150°C, 165°C, 175°C, 185°C, 190°C, 185°C and 180°C, respectively, and the rotation speed was 260r / min.
[0063] According to GB / T1040-2018 and ASTM D3985 standards, the high barrier composites of the isolation structures prepared in Examples 1-8 and the degradable composites prepared in Comparative Examples 1-5 were tested for tensile properties and oxygen permeability, respectively. The test results are shown in Table 1.
[0064] Table 1 Comparison of mechanical properties and oxygen barrier properties of composites
[0065]
[0066] It can be seen from Table 1 that the 50PLA-1.5T degradable high-barrier composite prepared in Example 3 of the present invention has the best mechanical properties and oxygen barrier properties.
[0067] Compared with Example 1 and Example 2, as the OMMT content increases from 0.5 parts to 1.5 parts, the mechanical strength and modulus of the composite do not change much, the elongation at break increases significantly, and the barrier performance to oxygen is enhanced. It can be seen that with the addition of OMMT, a clear isolation structure can be constructed inside the composite material to reduce the interfacial tension between PLA and PPC, while improving the diffusion path of gas molecules, effectively improving the tensile toughness and oxygen barrier performance of the composite material. Compared with Example 3, as the OMMT content increases from 1.5 parts to 3 parts, the oxygen barrier performance of the composite decreases slightly due to partial aggregation of OMMT. In Example 5, the content of OMMT is increased to 5 parts, which is easy to cause OMMT to aggregate inside the matrix. The unevenly dispersed OMMT has limited effect on improving the gas barrier performance, and the oxygen barrier performance is slightly worse than that of Example 3. In Example 6, Example 7 and Example 8, the content of PPC with better barrier performance and toughness in the blend gradually decreases, and the oxygen barrier performance and tensile toughness of the composite gradually decrease.
[0068] In Comparative Example 1, after PLA and PPC are directly melt-blended, the resulting blend is severely brittle and has poor gas barrier properties. This is because the interfacial bonding between PLA and PPC is poor, and the mechanical properties and gas barrier properties of the resulting blend are both poor. In Comparative Example 2, PLA and OMMT are directly blended, but the gas barrier properties of the PLA material cannot be effectively improved. In Comparative Example 3, OMMT-modified PLA is compounded with PPC, which also fails to significantly improve the barrier properties of the blend. In Comparative Example 4, OMMT is added to the blend of PLA and PPC by a one-step blending method. Since the interlamellar spacing of OMMT is not significantly improved, and the aggregation of OMMT in the composite is difficult to increase the permeation path of gas molecules, the gas barrier property of the blend is improved. The effect is limited.
[0069] The composites prepared in Example 3, Comparative Example 3 and Comparative Example 4 were subjected to X-ray scanning, and the results were as follows: Figure 1 As shown in the X-ray diffraction diagram, it can be seen that in the 50PLA-1.5T composite prepared in Example 3, the OMMT interlamellar spacing increases to about 3.39nm, while in the composites prepared in Comparative Examples 3 and 4, the OMMT interlamellar spacing is only 3.27nm. This is mainly because the PPC surface energy is closer to OMMT, and it can be more effectively inserted into the OMMT interlamellar during the pre-blending process, thereby increasing the OMMT interlamellar spacing, thereby more effectively increasing the permeation path of gas molecules, thereby improving the oxygen barrier performance of the composite.
[0070] Furthermore, SEM scanning was performed on the cross sections of the composites prepared in Example 3, Comparative Example 3 and Comparative Example 4. The results are as follows: Figure 2As shown. It can be clearly seen from the SEM image that the cross-sectional surface of the composite prepared in Example 3 is uniform, and OMMT is preferentially dispersed in the PPC phase and at the interface between PLA and PPC, so that the inorganic sheet with good barrier properties can effectively increase the permeation path of gas molecules. At the same time, the uniformly dispersed OMMT can increase the melt viscosity of PPC and make it close to the melt viscosity of PLA. When the modified PPC and PLA are blended again, PPC is easy to form an interpenetrating structure with PLA, and OMMT migrates to the interface between PLA and PPC, thereby forming a high-performance composite material with an isolation structure, which effectively improves the permeation path of gas molecules. The cross-sectional surfaces of the composite materials prepared in Comparative Examples 3 and 4 all have holes and clear phase interfaces to varying degrees, all of which are caused to varying degrees by the poor dispersibility of OMMT in the matrix, the weak bonding ability of the polymer matrix phase interface, and the large difference in melt viscosity between the polymer components. Therefore, it is not conducive to the improvement of the mechanical properties and gas barrier properties of the composite material.
[0071] The above description is only the best embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A PLA and PPC composite material with an isolation structure, characterized in that: The raw materials include, by weight: 30-70 parts of PLA, 30-70 parts of PPC and 0.5-5 parts of OMMT, and the total weight of the PLA and PPC is 100 parts; The preparation method comprises the following steps: pre-melting and extruding PPC and OMMT to obtain modified PPC; and then mixing PLA and the modified PPC to obtain a PLA and PPC composite material with an isolation structure.
2. The PLA and PPC composite material with an isolation structure as claimed in claim 1, characterized in that: The raw materials include, by weight: 50 parts of PLA, 50 parts of PPC and 1.5 parts of OMMT.
3. The method for preparing a PLA and PPC composite material with an isolation structure according to claim 1 or 2, characterized in that: The method comprises the following steps: pre-melting PPC and OMMT and extruding and granulating them to obtain modified PPC; and then mixing PLA and the modified PPC and extruding and granulating them to obtain a PLA and PPC composite material with an isolation structure.
4. The method according to claim 3, characterized in that PPC and OMMT are pre-melted and extruded into granules, wherein the extruder adopts a staged heating method from the feeding zone to the head zone, which is divided into seven sections, the temperature of zone one is 70-100°C, the temperature of zone two is 90-120°C, the temperature of zone three is 110-140°C, the temperature of zone four is 130-145°C, the temperature of zone five is 135-150°C, the temperature of zone six is 130-145°C, the temperature of zone seven is 125-145°C, and the screw speed is 350-500r / min.
5. The method according to claim 3, characterized in that PLA and modified PPC are mixed and extruded into granules, wherein the extruder adopts a staged heating method from the feeding zone to the head zone, which is divided into seven sections, the temperature of zone one is 130-150°C, the temperature of zone two is 150-165°C, the temperature of zone three is 160-180°C, the temperature of zone four is 160-185°C, the temperature of zone five is 165-200°C, the temperature of zone six is 160-190°C, the temperature of zone seven is 160-185°C, and the screw speed is 200-500r / min.
Citation Information
Patent Citations
Polylactic acid / core-shell structure composite material and preparation method thereof
CN103571164A